MicroRNA‐455 suppresses non‐small cell lung cancer through targeting ZEB1. (23rd March 2016) - Li, Ying‐Jie; Ping, Chen; Tang, Jian; Zhang, Wen
Abstract: MicroRNA‐455 (miRNA‐455), which is downregulated in human cancer, potently mediates the multiple steps of carcinogenesis. However, the role of miR‐455 in non‐small cell lung cancer (NSCLC) carcinogenesis remains unclear. In present study, we determined the mature miRNA‐455 expression in NSCLC tissues and cells by real‐time PCR. Follow‐up studies examined the effects of a miR‐455 mimic (gain of function) on cell proliferation, migration, and invasion. Our data indicate that miR‐455 was significantly down‐regulated in NSCLC cell lines and tissues. In functional assays, overexpression of miR‐455 suppressed the proliferation, migration, and invasion of NSCLC cell lines. Data from reporter assays showed that miR‐455 directly binds to 3′UTR of ZEB1 and suppresses the endogenous level of ZEB1 protein expression. Furthermore, overexpression of ZEB1 reverses miR‐455‐suppressed malignant phenotype of NSCLC cells. Moreover, we found that upregulation of ZEB1 expression is inversely associated with miR‐455 expression in NSCLC tissues. Taken together, miR‐455 as an anti‐oncogene in non‐small cell lung cancer through up‐regulation of ZEB1 and serve as a potential therapeutic target in NSCLC.